Comparison of Ultimate Capacities of RC Chimney Sections under Wind Loading - Bhatt, Megha; Vasanwala, Sandip (Trends in Sciences, 2022)
Diffusion of gaseous and particulate pollutants from tall stacks has formed an important element in the control of air pollution since the industrial revolution began. These tall reinforced concrete chimneys are considered to be cantilever columns subjected to axial load resulted from the self-weight of the shell, linings and other accessories and bending moments which are resulted from the lateral loads like wind forces and earthquake forces. The recently published IS: 4998 – 2015 adopted a limit state design concept which requires well defined stress-strain relationship for concrete and steel. It has been seen that there are many disparities lies between the stress-strain relationships of constituent materials adopted by IS: 4998 – 2015 and other design standards. This paper discusses various methods pertaining to the estimation of the ultimate strength of thin-walled hollow circular sections of reinforced concrete chimneys, subjected to wind loading. A comparative study of various methods based on the prevalent codes reveals considerable disparity in the predicted ultimate strength values. These differences have been critically analyzed and results are discussed in this paper in terms of ultimate strength along with the contribution of concrete and steel, ultimate curvature and depth of neutral axis. For the comparison of above-mentioned parameters, design recommendations of IS 4998 – 2015, CICIND 2011, ACI 307 – 08 are used. HIGHLIGHTS The recently published IS: 4998 – 2015 adopted a limit state design concept which requires well defined stress-strain relationship for concrete and steel which differs in terms of strain and stress limits when compared with other well established RC chimney design codes Various methods pertaining to the estimation of the ultimate strength of thin-walled hollow circular sections of reinforced concrete chimneys, subjected to wind loading are discussed using a comparative study with different parameters of RC chimney For the comparison of above-mentioned parameters, design recommendations of IS 4998 – 2015, CICIND 2011, ACI 307 – 08 are used Stress-strain relationship of concrete and steel also discussed with the bases of the same is also discussed in detail for each of the above codes GRAPHICAL ABSTRACT